Long-term physical training system design for athletes with musculoskeletal and visual system disorders - Deryabina, G. I.; Lerner, V. L.; Makarova, L. N. (Theory and Practice of Physical Culture, 2019)
Presently the global sport communities give a growing priority to adaptive sports including Paralympic sports. The article analyzes the long-term physical training system design options for the athletes diagnosed with musculoskeletal and visual system disorders. The study makes an emphasis on the systemic individualized design options with the relevant provisions for the long-term customizable physical training system with the coordination development component under the traditional physical education system. The design shall provide for the necessary motor experience and its employment success in response to the environmental challenges; prevent the degenerating processes triggered by the analyzer system malfunctions; address the disorder zones revealed by the coordination ability tests; improve the auditory functions, discrimination abilities and sensitivity to rhythmic patterns associated with physical activity; set the individual and team athletic progress trends; and address the physical and sensor asymmetries in the coordination qualities development process.